Unveiling cancer crosstalk: Mapping complexity across time and space. - Yibin Kang (PLoS Biology)
Cancer evolves through dynamic exchanges with its environment, harnessing these interactions to grow, adapt, and transcend the constraints that would otherwise limit its progress. A new collection of articles explores this tumor-environment crosstalk across temporal and spatial scales.